2001
DOI: 10.1034/j.1398-9995.2001.00086.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of contact allergy in adults

Abstract: It is concluded that contact allergy is influenced by sociodemographic parameters and plays an important role in the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
227
4
27

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 328 publications
(277 citation statements)
references
References 18 publications
19
227
4
27
Order By: Relevance
“…Marinovic-Kulisic et al [18] found that most common allergens were of similar relevance in contact dermatitis, regardless of the patients' age and sex. In contrast, the results of a German study indicated that contact dermatitis was more frequent in women than in men (50.2% vs. 29.9%, OR 2.36, CI 1.84-3.03), and that this involved fragrance mix, nickel, turpentine, cobalt chloride and thimerosal [19]. Gender-related drug allergy patterns have not been thoroughly studied, and the issue is awaiting further elucidation.…”
Section: Discussionmentioning
confidence: 49%
“…Marinovic-Kulisic et al [18] found that most common allergens were of similar relevance in contact dermatitis, regardless of the patients' age and sex. In contrast, the results of a German study indicated that contact dermatitis was more frequent in women than in men (50.2% vs. 29.9%, OR 2.36, CI 1.84-3.03), and that this involved fragrance mix, nickel, turpentine, cobalt chloride and thimerosal [19]. Gender-related drug allergy patterns have not been thoroughly studied, and the issue is awaiting further elucidation.…”
Section: Discussionmentioning
confidence: 49%
“…In Finland, the prevalence of Cr(VI) sensitivity among 822 human volunteers was found to be 1.7% (4) and in Germany the prevalence in an unselected population of 1141 adults was 1.1% (22).…”
Section: Epidemiologymentioning
confidence: 98%
“…In many parts of the world, more than 20% of the adult population are suffering from contact allergy (2,4). It is a well-known occupational risk in health care personnel, metal workers, brick layers and hairdressers (2,5).…”
Section: Allergic Contact Sensitization In a General Population Intromentioning
confidence: 99%